Prenatal care and infant outcomes of teenage births: a Project WATCH study - Madelin E. Gardner; Amna Umer; Toni Rudisill; Brian Hendricks; Candice Lefeber; Collin John; Christa Lilly (BMC, 2023)
Abstract Introduction Infants of teenage births are known to have increased risk of poor infant outcomes. Adequate prenatal care (PNC) is essential to the overall health of infants and their birthing persons. While teenage births continue to be of concern in rural areas, little is known about the association between inadequate PNC and poor infant outcomes in teenage populations. Purpose To determine the association between inadequate PNC (< 10 visits) and poor infant outcomes neonatal intensive care unit (NICU) stay, low APGAR score, small for gestational age (SGA) and length of stay (LOS). Methods The study used West Virginia (WV) Project WATCH population level data (May 2018-March 2022). Multiple logistic regressions and survival analysis were performed on infant outcomes; NICU stay, APGAR score, infant size, and infant length of stay (LOS) with PNC categories inadequate (< 10 PNC visits) vs adequate (10 or more) adjusting for covariates including maternal race, insurance status, parity, smoking status, substance use status, and diabetes status. Results Of births to teenagers, 14% received inadequate PNC. Teens who received inadequate PNC had increased odds of infant admitted to NICU (aOR: 1.84, CI:(1.41, 2.42), p < 0.0001), low 5- minute APGAR score (aOR: 3.26, CI:(2.03,5.22), p < 0.0001), and increased LOS (Est. = -0.33, HR: 0.72, CI:(0.65,0.81), p < 0.0001). Conclusions Results demonstrated that infants of teenagers who received inadequate PNC are at increased risk of requiring a NICU stay, having a low APGAR score and requiring an increased LOS. PNC is particularly important for these groups as they are at increased risk of poor birth outcomes.